Development of E-Comic Based on Local Wisdom to Improve Scientific Literacy - Brian Priyangga; Sarwi Sarwi; Arif Widiyatmoko; Elda Herlina; Putut Marwoto; Woro Sumarni (Ta'dib, 2022)
This research is the development of local wisdom-based e-comics to increase scientific literacy. Learning media can help achieve learning objectives. This study aims to develop e-comic learning media based on local wisdom to improve scientific literacy in grade IV elementary school. The type of research used is Research and Development with the ADDIE development model namely Analyze, Design, Development, Implementation, and Evaluation. This study used test subjects by carrying out validity tests on media experts, material experts, learning experts and the responses of ten fourth grade elementary school students. Data collection using a questionnaire instrument. Research data were analyzed by means of descriptive quantitative and descriptive qualitative. The results of the media expert validator are categorized as very valid. The results of the material expert validator are categorized as very valid. The results of the learning expert validator are categorized as very valid. As well as the results of the responses of ten fourth grade elementary school students categorized as very valid. The overall results of the validator test are categorized as very valid so that e-comic media based on local wisdom can be used with learning alternative energy sources in grade IV Elementary School Science lessons.